Efficacy of Metarhizium rileyi and Beauveria bassiana as Biocontrol Agents against Third-Instar Spodoptera frugiperda under Laboratory Conditions - Yashaswini, G; Upendhar, S; Sree, K Vani; Triveni, S; Vanisri, S (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Managing the Fall Armyworm, Spodoptera frugiperda (J. E. Smith), a significant pest affecting maize, has become challenging due to widespread restrictions on synthetic pesticide use and the emergence of insecticide-resistant populations. As a sustainable alternative, entomopathogenic fungi have shown promise as biological control agents against S. frugiperda. In this study, commercial formulations of two fungal biocontrol agents, Metarhizium rileyi (Mr-18 strain) and Beauveria bassiana (Bb-52 strain), were assessed against third-instar larvae of S. frugiperda under laboratory conditions. Results showed that both M. rileyi and B. bassiana were similarly effective, with M. rileyi exhibiting a slightly lower LC50 value (1.648 x 10⁵ ppm) compared to B. bassiana (2.203 x 10⁵ ppm), particularly in populations from Telangana. These results highlight the potential of using effective strains of B. bassiana and M. rileyi at a concentration of 1 x 10⁵ conidia/ml as viable biocontrol strategies against S. frugiperda.